Natural abilities for Agricultural Development in Shaqlawa District (Raparin Journal of Humanities (RJH), 2023)
Shaqlawa District, one of the districts of Erbil Governorate, which plays an important role in the agricultural sector, as it possesses a range of important natural resources that have a direct impact on agricultural development in the district. The main objective of the research is to present the natural ability of the region and its role in development between 2010 and 2020 and to show its positive and negative role in the process In order to obtain the goal of the research, we relied on the data and statistics of the Directorate of Agriculture of Arbil and the Division of Agriculture (Shaqlawa, Harir and Balisan) and the researcher relied on the preparation of research maps on geographic information systems (GIS) and finally we reached the following conclusion, the natural capabilities authorized by the region have a direct impact on the production of a large quantity of agricultural products annually.